The Court & the Cataracts: The Creation of the Queen Victoria Niagara Falls Park and the Ontario Court of Appeal - Wentzell, Tyler (Ontario History)

(untitled) (The Ontario Historical Society, 2014)
The establishment of the Queen Victoria Niagara Falls Park involved an extensive expropriation by the Government of Ontario. The perceived social value of parks had been increasing in recent years, but this was the first time in Canada that private land had been expropriated in order to create a park. The majority of the land owners engaged in arbitration, while three land owners took their objections as far as the Ontario Court of Appeal. The enacting legislation along with these proceedings provide unique insight into life around the falls, the role of the Ontario Court of Appeal, and the nature of expropriation and the establishment of parks in late nineteenth century Ontario.